A Preliminary Study of Percentage Breast Glandularity of Bangladeshi Women from Mammography Data - Meherun Nahar; Md. Sazzad Hossain; Abdus Sattar Mollah; Mir Md. Akramuzzamsan (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2016)
Abstract: A study was made to estimate mammographic breast glandularity in Bangladeshi women from generic radiographic data. The primary objective of this study was to determine the percentage of breast glandularity of Bangladeshi women which will affect mean glandular dose (MGD) during diagnostic mammography. The secondary objective was to evaluate some of the factors affecting women’s glandular tissue. A fitted equation was applied for 80 women who underwent diagnostic mammography. The values of compressed breast thickness (CBT), mAs and target/filter combination, were collected for 80 women ranging in age from 21 to 70. The average breast glandularity of the study sample was 43.7% ± 17.35%. Breast glandularity was found to decrease with breast thickness and age. No significant variation of mean glandularity has been found with Body Mass Index (BMI).